Revisión de las ecuaciones para el cálculo de flujo turbulento hidráulicamente liso en tuberías plásticas (2017)
Smooth materials, such as plastic and PVC, are currently the most extensively used in water distribution networks, whereas Years ago, rougher materials, such as concrete, were used to build this type of networks. It was with these type of materials that the design equations were deducted, taking into consideration all of their physical properties, which are widely different than those of modern day materials. For this reason, this work uses PVC as a material to verify the applicability of these equations, measuring the pressure loss in different installations with a Reynolds number that ranged between 5x10^4 and 5x10^5 and relative roughness between 6x10^-4 and 2x10^-3, for this are the ranges in which the designs based on the recommendations of the standards should be. The results are displayed graphically, relating the friction factor with the Reynolds number. And, it is found that for small diameters, different equations can be used to have an adequate estimate of the friction factor, whereas for larger diameters, the Colebrook-White equation can best describe the relationship between the friction factor and the Reynolds number correctly. Additionally, equations like the Hazen-Williams presented good approximations, provided they are used considering their limits of applicability.--Tomado del Formato de Documento de Grado.